Event-triggered cooperative control for high-order nonlinear multi-agent systems with finite-time consensus - Gong, Shiyin; Zheng, Meirong; Hu, Jing; Zhang, Anguo (Zielona Góra: Uniwersytet Zielonogórski)
An event-triggered adaptive control algorithm is proposed for cooperative tracking control of high-order nonlinear multiagent systems (MASs) with prescribed performance and full-state constraints. The algorithm combines dynamic surface technology and the backstepping recursive design method, with radial basis function neural networks (RBFNNs) used to approximate the unknown nonlinearity. The barrier Lyapunov function and finite-time stability theory are employed to prove that all agent states are semi-globally uniform and ultimately bounded, with the tracking error converging to a bounded neighborhood of zero in a finite time. Numerical simulations are provided to demonstrate the effectiveness of the proposed control scheme.
Keywords: multi-agent systems; cooperative control; event-triggered control; neuro-adaptive control; prescribed performance